Interlaboratory evaluation of Enterococcus faecium NRRL B-2354 as a Salmonella surrogate for validating thermal treatment of multiple low-moisture foods - Ahmad, Nurul Hawa; M. Hildebrandt, Ian; R. Pickens, Shannon; Vasquez, Sabrina; Yuqiao, Jin; Shuxiang, Liu (Elsevier, 2022)
This multi-institutional study assessed the efficacy of Enterococcus faecium NRRL B-2354 as a nonpathogenic Salmonella surrogate for thermal processing of nonfat dry milk powder, peanut butter, almond meal, wheat flour, ground black pepper, and date paste. Each product was analyzed by two laboratories (five independent laboratories total), with the lead laboratory inoculating (E. faecium or a five-strain Salmonella enterica serovar cocktail of Agona, Reading, Tennessee, Mbandaka, and Montevideo) and equilibrating the product to the target water activity before shipping. Both laboratories subjected samples to three isothermal treatments (between 65 and 100°C). A log-linear and Bigelow model was fit to survivor data via one-step regression. On the basis of D80°C values estimated from the combined model, E. faecium was more thermally resistant (P < 0.05) than Salmonella in nonfat dry milk powder (DEf-80°C, 100.2 ± 5.8 min; DSal-80°C, 28.9 ± 1.0 min), peanut butter (DEf-80°C, 133.5 ± 3.1 min; DSal-80°C, 57.6 ± 1.5 min), almond meal (DEf-80°C, 34.2 ± 0.4 min; DSal-80°C, 26.1 ± 0.2 min), ground black pepper (DEf-80°C, 3.2 ± 0.8 min; DSal-80°C, 1.5 ± 0.1 min), and date paste (DEf-80°C, 1.5 ± 0.0 min; DSal-80°C, 0.5 ± 0.0 min). Although the combined laboratory D80°C for E. faecium was lower (P < 0.05) than for Salmonella in wheat flour (DEf-80°C, 9.4 ± 0.1 min; DSal-80°C, 10.1 ± 0.2 min), the difference was ~7%. The zT values for Salmonella in all products and for E. faecium in milk powder, almond meal, and date paste were not different (P > 0.05) between laboratories. Therefore, this study demonstrated the impact of standardized methodologies on repeatability of microbial inactivation results. Overall, E. faecium NRRL B-2354 was more thermally resistant than Salmonella, which provides support for utilizing E. faecium as a surrogate for validating thermal processing of multiple low-moisture products. However, product composition should always be considered before making that decision.